2019
DOI: 10.1007/s10286-019-00606-y
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide to active stand testing and analysis using continuous beat-to-beat non-invasive blood pressure monitoring

Abstract: R. (2019). A practical guide to active stand testing and analysis using continuous beat-to-beat non-invasive blood pressure monitoring. Clinical autonomic research, 29(4), 427-441.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 64 publications
2
92
1
6
Order By: Relevance
“…In addition, the intervention had no effect on ADAS-cog scores ( 26 ), but in the substudy, we found an effect of nilvadipine on hippocampal cerebral blood flow ( 50 ). A particular strength of this study is the use of continuous beat-to-beat finger arterial BP measurements instead of the traditional arm-cuff-based approaches, which allows capturing transient information instead of steady-state measurements ( 51 ). The initial drop in BP upon standing in our study (±18/9 mm Hg) was smaller compared with previous studies, for example, in the normative data of people aged 70–79 years from TILDA (±40/25 mm Hg) ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the intervention had no effect on ADAS-cog scores ( 26 ), but in the substudy, we found an effect of nilvadipine on hippocampal cerebral blood flow ( 50 ). A particular strength of this study is the use of continuous beat-to-beat finger arterial BP measurements instead of the traditional arm-cuff-based approaches, which allows capturing transient information instead of steady-state measurements ( 51 ). The initial drop in BP upon standing in our study (±18/9 mm Hg) was smaller compared with previous studies, for example, in the normative data of people aged 70–79 years from TILDA (±40/25 mm Hg) ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was used to derive measures of heart rate variability (HRV) during supine resting and provocative testing. A detailed description of continuous blood pressure (BP) monitoring using beat-to-beat systolic BP, diastolic BP and pulse rate using the volume clamp method (Finometer NOVA, FMS Medical Systems, Arnheim, Netherlands) during autonomic testing is available elsewhere [32]. Briefly, a pressure cuff was applied to the patient (left hand, middle finger) with height correction.…”
Section: Autonomic Testingmentioning
confidence: 99%
“…perpetuity. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted December 8, 2020. ; https://doi.org/10.1101/2020.12.07.20241109 doi: medRxiv preprint et al 2017; Wieling et al 1992;Smith, Porth, and Erickson 1994;Finucane et al 2019). These responses are characteristic of an aging autonomic nervous system and are evident here.…”
Section: Discussionmentioning
confidence: 52%